Criminal Responsibility of Road Organizers as An Effort to Prevent Traffic Accident - Amelia Arif; Andi Istiana Inayah Dwi Putri Putri (PT. Riset Press International, 2026)
Traffic accidents in Indonesia remain a serious problem with high mortality rates. Inadequate road infrastructure conditions are one of the main contributing factors to accidents. This study aims to analyze the criminal liability of road organizers in the context of traffic accident prevention based on Indonesian positive law provisions. The research method used is normative juridical with statutory and conceptual approaches. Secondary data was collected through literature study and analyzed qualitatively. The results show that the criminal liability of road organizers is regulated in Article 273 of Law Number 22 of 2009 concerning Road Traffic and Transportation, but its implementation remains weak due to minimal law enforcement. Road organizers can be held criminally liable if their negligence in road maintenance or construction is proven to cause accidents. To optimize accident prevention, it is necessary to strengthen supervision systems, improve the competence of road organizers, and enforce consistent and firm law enforcement against violations of road safety standards.